Analisis Tematik Subjek Dakwah Dalam Al-Quran - Dianto, Icol (Tadbir: Jurnal Manajemen Dakwah FDIK IAIN Padangsidimpuan, 2019)
Da'wah is an activity to invite people to go straight (right path) based on the Quran and Sunnah of the Prophet. Da'wah gets its existence in the Quran that appears with various variants. This article aims to uncover the variants of the word preaching in the Quran by using thematic analysis of the subject of preaching in the Quran. The study results show that in the Quran the da'wah was carried out by God, angels, demons and humans. Da'wah subjects from the human class can be carried out by believers, Mushrikin and liars. Furthermore, the da'wah subjects of the human group appear in groups, and institutions: formal and informal. From the discussion on the subject of da'wah, the subject of that da'wah is essentially the prophet who is in the Quran.Keywords: Dai, Missionary, Da'wah Subjects, Ulama.AbstrakDakwah merupakan kegiatan mengajak manusia ke jalan lurus (sirath al-mustaqim) berdasarkan panduan al-Quran dan Sunnah Nabi. Dakwah mendapatkan eksistensinya dalam al-Quran yang muncul dengan berbagai variannya. Artikel ini bertujuan untuk mengungkap varian kata dakwah dalam al-Quran dengan menggunakan analisis tematik subjek dakwah dalam al-Quran. Hasil kajian menunjukan bahwa dalam al-Quran dakwah itu dilakukan oleh Allah, malaikat, setan dan manusia. Subjek dakwah dari golongan manusia dapat dilakukan oleh mukminin, musyrikin dan pendusta. Selanjutnya, subjek dakwah dari golongan manusia muncul dalam bentuk berkelompok, dan lembaga: formal dan non-formal. Dari pembahasan tentang subjek dakwah, yang menjadi subjek dakwah itu pada hakikatnya adalah nabi yang berakhlakan al- Quran.Kata Kunci: Dai, Mubaligh, Subjek Dakwah, Ulama.